The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/catal10111236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Solvent on the Basic Properties of Mg–Al Hydrotalcite Catalysts for Glucose Isomerization

Abstract: We suggested the existence of a relationship between the base properties of Mg–Al hydrotalcite catalysts and the solvents employed in the industrially important isomerization of glucose produce fructose. We prepared Mg–Al hydrotalcite catalysts with different Mg/Al atomic ratios to tune the basic properties of the catalyst. The prepared catalysts were used in the glucose isomerization conducted in various solvents. Experimental results confirmed that the catalysts exhibited different activities in the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…It also reveals relatively obvious hexagon overlapping crystals, which are typical for LDHs. The morphology features do not change after the adsorption and are similar to those observed in previous studies [14,30,36].…”
Section: Evaluation Of Metal Content In Adsorbed Mg-al Ldhsupporting
confidence: 89%
“…It also reveals relatively obvious hexagon overlapping crystals, which are typical for LDHs. The morphology features do not change after the adsorption and are similar to those observed in previous studies [14,30,36].…”
Section: Evaluation Of Metal Content In Adsorbed Mg-al Ldhsupporting
confidence: 89%
“…The catalytical activity of solid basic hydrotalcite catalysts for glucose–fructose isomerisation has been found to depend on the surface properties of the catalysts, which in turn are affected by the solvent. 49 The solvent also affects the ionisation constants of sugars as well as the rate-limiting formation and stability of the enediol anion intermediate formed during base-catalysed glucose–fructose isomerisation with e.g. amines.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have investigated the effect of non‐aqueous solvents on glucose‐fructose isomerization because non‐aqueous solvents can improve solubilities of reactants/products, conversion rates, and selectivities to desired products [73–74] . Such non‐aqueous solvents include alcohols, [34,75] DMSO, [76] and DMA [77–78] . Yabushita et al [79] .…”
Section: Discussionmentioning
confidence: 99%
“…[73][74] Such non-aqueous solvents include alcohols, [34,75] DMSO, [76] and DMA. [77][78] Yabushita et al [79] reported superior fructose selectivity (> 78%) and glucose conversion (> 55%) by MgÀ Al hydrotalcite in primary alcohols (methanol, ethanol, and 1-propanol) to those in water at 90 °C for 2 h. de Mello et al [26] modulated UiO-66(Zr) to create Lewis acid sites for glucose isomerization in alcohols. They found that reaction in 1propanol gave the highest fructose selectivity of 73% at 82% glucose conversion.…”
Section: Discussionmentioning
confidence: 99%